FRI0352B COMPARISON OF TWO ILOPROST REGIMENS IN TERMS OF ECONOMIC IMPACT AND EFFECTIVENESS. (June 2019) - Rossa, Alessandra Della; Barsotti, Simone; Battista, Marco DI; Puccetti, Lorenzo; Lorenzoni, Valentina; Turchetti, Giuseppe; Mosca, Marta
Abstract : Background: Systemic sclerosis (SSc) is an autoimmune chronic disease characterized by prominent vascular involvement. Intravenous iloprost (IV ILO), according to the recently updated EULAR recommendations, is indicated for Ssc Raynaud's phenomenon (RP) after failure of oral therapy. Moreover, IV ILO could be useful in DU healing and may represent a potential disease modifying medication. However, there are no uniform data regarding type of regimen (dosage, duration and frequency) and infusion modality. Objectives: The purpose of this study was to compare effectiveness (in terms of Dus) and direct costs, of two regimens of IV ILO infusion in the same cohort of consecutive SSc subjects. Methods: Protocol A (A): the patient was admitted and 100 mcg of ILO was diluted in 500 ml of normal saline or 5% dextrose solution and infused continually at the maximum tolerated dose until exhaustion. Protocol B (B): the patient was followed as outpatient at infusion clinic and 50 mcg of ILO was diluted in 250 of normal saline or 5% dextrose and infused at a dose range from 0.5 to 1.5 ng/Kg/min. The dose was escalated at 30 minutes intervals and maintained at the maximum tolerated dose for 5 consecutive hours for two consecutive days. The intervals between the infusions were between 6-8 weeks in both protocols depending on clinical response and availability of places at the Unit. 44 patients who received long term IV ILO as inpatients (Cohort A), after a wash out of 3 months, were switched to ambulatory administration (Cohort B). Thereafter, after one year of follow-up 24 patients of the protocol B were lost to follow-up and 20 patients were maintained on this regimen. Comparison was made between Cohort A (44 patients=A44) in the period between march 2015 and October 2016 (period A), Cohort B (44 patients=B44) between October 2016 and March 2017 (period B44), Cohort B (20 patients=B20), between October 2017 and March 2018 (period B20). Comparison between groups was made by non parametric tests and contingency table analysis when appropriate. Costs were estimated multiplying data related to resource use (drug consumpion, hospital stay, outpatient visits, management of complications, etc) by unit cost obtained from the accounting office of the Hospital. All costs were expressed in Euro Results: Mean number of DUs at the end of period A was 0, 37±0, 98 in A44 as compared to 0, 90±1, 39 of period B44 cohort B44 (p=0, 045) and 0, 55±0, 95 of period B20 Cohort B20 (p=n.s.). Cumulative number of DUs was 9/44 in Cohort A (20.5%) as compared to 20/44 in Cohort B44 (45% p=0.002) and 7/20 in cohort B20 (35% p=0, 05). High number of drop outs (24/44) in protocol B was due mainly to statistical significant difference in tolerability (adverse events 11% protocol A vs 42% protocol B p < 0, 01). Direct costs were higher in protocol A (3132±883 Euros vs 2687±556 Euros) as compared to protocol B, despite the differences were not statistically significant between the two modalities Conclusion: Protocol A seems to represent a regimen better tolerated and more effective than protocol B. Moreover, protocol B is affected by high rate of drops out due mainly to worse tolerability. Admitting SSc-patients for continuous IV ILO infusion seems to represent a better tolerated and more effective choice than following them as outpatients at infusion clinic, with substantially comparable direct costs in the same SSc cohort. Disclosure of Interests: Alessandra Della Rossa: None declared, Simone Barsotti: None declared, Marco Di Battista: None declared, Lorenzo Puccetti: None declared, Valentina Lorenzoni: None declared, Giuseppe Turchetti: None declared, Marta Mosca Paid instructor for: GlaxoSmithKline, Lilly, UCB